2010
DOI: 10.1016/j.urology.2009.11.022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Epigenetic Therapy on Congenital Neurogenic Bladders—A Pilot Study

Abstract: OBJECTIVES-To demonstrate that human smooth muscle cells derived from neurogenic bladders produce more collagen in vitro than smooth muscle cells derived from normal bladders, and that epigenetic therapy may normalize this increased collagen production.METHODS-Human smooth muscle cells from normal (n = 3) and neurogenic bladders (n = 3) were cultured in normal culture media and at different concentrations of the histone deacetylase inhibitors trichostatin A, valproic acid, and the DNA methylation inhibitor 5-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Visceral SMC from neurogenic bladder possess a synthetic phenotype (producing more collagen than normal SMC). This collagen-production has been shown to be inhibited by 5′-aza-deoxycytidine, an inhibitor of DNA methylation [47]. Neurogenic compared to normal bladder SMC also proliferate at a higher rate and continue to express unique expression patterns, even after many passages [48], [49].…”
Section: Introductionmentioning
confidence: 99%
“…Visceral SMC from neurogenic bladder possess a synthetic phenotype (producing more collagen than normal SMC). This collagen-production has been shown to be inhibited by 5′-aza-deoxycytidine, an inhibitor of DNA methylation [47]. Neurogenic compared to normal bladder SMC also proliferate at a higher rate and continue to express unique expression patterns, even after many passages [48], [49].…”
Section: Introductionmentioning
confidence: 99%
“…The DNA methylation inhibitor, 5-Aza, was shown to partially inhibit collagen type I and III genes in visceral SMC isolated from neurogenic bladders [60]. Furthermore, 5-Aza attenuated PDGF-induced airway SMC migration and proliferation, and was able to increase cellular contractility [61].…”
Section: Role Of Epigenetics In Regulating Smc Plasticitymentioning
confidence: 99%
“…12 Recent studies have demonstrated that HDACs are involved in tissue fibrosis in various organs, including urinary bladder, kidney, liver, heart and lung. 10,13,14 In addition, small-molecule inhibitors of HDAC abrogate the activation and proliferation of fibroblasts in vitro and lessen tissue fibrosis in vivo. 10,13 Although the exact mechanisms by which HDAC mediates fibrotic responses remain largely unknown, HDAC inhibitors are known to repress the TGF-b pathway.…”
Section: Introductionmentioning
confidence: 99%
“…10,13,14 In addition, small-molecule inhibitors of HDAC abrogate the activation and proliferation of fibroblasts in vitro and lessen tissue fibrosis in vivo. 10,13 Although the exact mechanisms by which HDAC mediates fibrotic responses remain largely unknown, HDAC inhibitors are known to repress the TGF-b pathway. 15 However, none of the currently available HDAC inhibitors is specific for a single isoform of HDAC, which increases toxicity and limits the clinical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation